Validation of multiplexed human papillomavirus serology using pseudovirions bound to heparin-coated beads - Faust, H.; Knekt, P.; Forslund, O.; Dillner, J. (Journal of general virology, 2010)
This study developed and validated a high-throughput human papillomavirus (HPV) serology method based on Luminex technology, using pseudovirions (PsVs) of eight mucosal HPV types (HPV-6, -11, -16, -18, -31, -45, -52 and -58) and two cutaneous HPV types (HPV-5 and -38) bound to heparin-coated beads. Analysis with neutralizing type-specific monoclonal antibodies against the included HPV types indicated the type specificity of the assay. Analysis of negative-control serum samples from 63 children and 71 middle-aged women with up to one lifetime sexual partner indicated high specificity. Positive-control serum samples from subjects with known HPV DNA status or clinical diagnosis found expected sensitivities for most of the HPV types in 219 European serum samples, but lower than expected in 124 samples from Africa. HPV-45 and -52 did not react as expected with the human serum samples. The PsV-Luminex method was used to determine the HPV-seropositivity-associated relative risk for future cervical cancer using 208 serum samples from a prospective study of 18 814 women followed for 23 years, analysed previously with standard HPV-16 ELISA. The PsV-Luminex method gave similar results to ELISA (kappa=0.77). As expected, HPV seropositivities assayed using the PsV-Luminex method found an increased risk of cervical cancer for HPV-16 [odds ratio (OR)=7.7, 95 % confidence interval (CI)=2.6-23] and HPV-31 (OR=4.1, 95 % CI=1.6-10.8), non-significant tendencies for increased risk for other mucosal HPV types and no risk for the cutaneous HPV types. In summary, multiplexed HPV serology using mammalian-derived PsVs selected for native conformation by binding to heparin-coated beads was validated as a high-throughput HPV serological method for most of the analysed HPV types.